Implementation of an inhaled nitric oxide protocol decreases direct cost associated with its use - Todd Tzanetos, Deanna R; Housley, Jon J; Barr, Frederick E; May, Warren L; Landers, Cheri D (Respiratory care, 2015)
The objective of this study was to determine whether the implementation of an inhaled nitric oxide protocol (INO) in a pediatric ICU (PICU) would reduce cost associated with its use without negatively affecting patient outcomes. This is a retrospective cohort study of 76 subjects who required INO therapy in the PICU during the study period. A nitric oxide setup and weaning protocol was implemented in the PICU. The medical records of subjects who had received INO 18 months after protocol implementation, as well as the medical records of subjects who had received INO in the 18 months before protocol implementation, were reviewed. Length of time on INO, cost of INO per subject, mortality, stay, and ventilator hours were recorded. There were 38 subjects in the pre-protocol group and 38 subjects in the post-protocol group. There was a statistically significant decrease in the median per subject cost of INO between the pre- and post-protocol groups (P < .01). There was no statistically significant difference in the median duration of INO use (P = .06), median PICU (P = .42) or hospital (P = .58) stay, median duration of mechanical ventilation (P = .79) or percent mortality (P = .28) between the 2 groups. Implementation of an INO setup and weaning protocol in a PICU reduces the cost associated with its use without a statistically significant difference in mortality. In an era of increased awareness regarding healthcare spending, implementation of evidence-based protocols can provide a way to ensure the judicious utilization of medical resources.